Correction: General criteria for evaluating suitable polymer ligands for the synthesis of aluminum nanocrystals. Issue 80 (30th September 2020) - Yu, Hua; Lu, Shaoyong; Gao, Huimin; Lu, Zhongyuan; Liu, Kun
Abstract : Correction for 'General criteria for evaluating suitable polymer ligands for the synthesis of aluminum nanocrystals' by Hua Yu et al., Chem. Commun., 2020, 56, 217–220, DOI: ; 10.1039/C9CC08476B .